Depth-wise attenuation mechanism of seismic waves in the Andaman region. Issue 151 (December 2021) - Dutta, Abhisek; Biswas, Rahul; Singh, Chandrani; Kumar, M. Ravi; Jana, Niptika; Singh, Arun
Abstract: This study evaluates the depth-dependent seismic wave attenuation characteristics in the Andaman region which is a part of the Andaman-Nicobar Subduction zone (ANSZ), and possible causes. We have analyzed seismic waveforms of 1402 earthquakes recorded at seven broadband seismic stations located over the Andaman Island, to estimate the direct S-wave ( Q s ), coda wave ( Q c ), intrinsic ( Q i ) and scattering ( Q sc ) attenuation parameters. The coda normalization method is used to calculate Q s . Additionally, the variation of Q c with frequency and coda window length is studied using the single back-scattering method. The separation of Q i and Q sc is achieved using the Wennerberg's method. Results show a strong frequency dependence of Q c and Q s . At 1 Hz, the values of Q c are 136, 137, 137 and 146 for coda window length of 30, 40, 50 and 60 s respectively, with the corresponding frequency-dependent coefficient ( n ) of 0.82, 0.83, 0.85 and 0.82. At 1 Hz the observed Q i values show a close proximity to Q c values, which indicates a strong dominance of intrinsic attenuation. Also, it is observed that Q 0 i shows low value and remains almost the same between 115 and 132 km depth, with a slight increase in between 132 − 140 km. The observed results imply high intrinsic attenuation, possibly due to partial melting or fluid-filled rocks at these depths. Whereas Q 0sc shows a different trend. It gradually increases up to a depth of 132 km, with a slight decrease beyond that. This indicates a decrease in heterogeneity up to 132 km and a slight increase in the same below that. Further, the estimates of pressure ( P ) and temperature ( T ) conditions of the subducting slab with depth show an increase in temperature from 996° to 1015°C and an increase in pressure from 33.8 to 41.2 kbar, as the depth increases from 115 to 140 km. The phase relationship for the basaltic rocks with 5 − 6 wt % bound H 2 O in eclogite facies reveals that the P − T condition observed in this study lies above the solidus temperature. This promotes the formation of interstitial liquid (5 − 10 % ) at these depths, probably causing high intrinsic attenuation. Highlights: Estimation of intrinsic and scattering attenuation for Andaman region. Investigating the dominant mechanism of attenuation properties in Andaman region. Qualitative estimation of subducting slab's physical condition using quality factors.